Is small tidal volume with low positive end expiratory pressure during one-lung ventilation an effective ventilation method for endoscopic thoracic surgery? - Yun, Du Gyun (Korean J Anesthesiol, 2014)
BACKGROUND: The present study will focus on the rationale for the use of small tidal volume with 6 cmH(2)O positive end expiratory pressure (PEEP) with the changes of arterial oxygen tension, plateau airway pressure, and static lung compliance during one lung ventilation for endoscopic thoracic surgery. METHODS: Forty-three patients were intubated with a double-lumen endobronchial tube. After positioning the patients in the lateral decubitus, one-lung ventilation was started with 100% oxygen, tidal volume 10 ml/kg without PEEP; arterial oxygen tension, plateau airway pressure, and static compliance were checked as baseline values (T0). Fifteen minutes later, same parameters were measured (T15). The tidal volume had changed to 6 ml/kg with 6 cmH(2)O PEEP. Fifteen minutes later, the same parameters were measured (T30). RESULTS: Oxygen tension had decreased at T15 (282.1 ± 83.4 mmHg) compared to T0 (477.2 ± 82.4 mmHg) (P < 0.0001), but was maintained at T30 (270.4 ± 81.9 mmHg). There was no difference in peak inspiratory pressure at T15 or T30 compared to T0, plateau airway pressure was increased at T15 and T30 (P < 0.05) and static lung compliance was decreased at T15 and T30 (P < 0.0001). CONCLUSIONS: In carrying out one-lung ventilation for thoracic surgery using an endoscope, the addition of a PEEP of 6 cmH(2)O in the dependent lung, while reducing the tidal volume of 6 ml/kg, both oxygen tension and lung compliance are maintained without increasing the plateau airway pressure. Protective lung ventilation is useful for one lung ventilation.